The Arabidopsis TAG1 Transposase Has an N-Terminal Zinc Finger DNA Binding Domain That Recognizes Distinct Subterminal Motifs - Mack, Alyson M. (American Society of Plant Biologists, 2001)
The in vitro DNA binding activity of the Arabidopsis Tag1 transposase (TAG1) was characterized to determine the mechanism of DNA recognition. In addition to terminal inverted repeats, the Tag1 element contains four different subterminal repeats that flank a transcribed region encoding a 729–amino acid protein. A single site-specific DNA binding domain is located near the N terminus of TAG1, between residues 21 and 133. This domain binds specifically to the AAACCC and TGACCC subterminal repeats, found near the 5′ and 3′ ends of the element, respectively. The ACCC sequence within these repeats is critical for recognition because mutations at positions 3, 5, and 6 abolished binding, yet the first two bases also are important because substitutions at these positions decreased binding by up to 90%. Weak interaction also occurs with the terminal inverted repeats, but no binding was observed to the other two 3′ subterminal repeat regions. Sequence analysis of the TAG1 DNA binding domain revealed a C(2)HC zinc finger motif. Tests for metal dependence showed that DNA binding activity was inhibited by divalent metal chelators and greatly enhanced by zinc. Furthermore, mutation of each cysteine residue predicted to be a metal ligand in the C(2)HC motif abolished DNA binding. Together, these data show that the DNA binding domain of TAG1 specifically binds to distinct subterminal repeats and contains a zinc finger.